تهجير أهل القاتل بين العرف الليبي وأحكام الشريعة الإسلامية: دراسة فقهية تأصيلية - بلعزي، سميرة حسن سالم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study investigates an important subject of Libyan traditions of forced displacement of the family of a convicted killer in Libyan tradition and the provision of the Islamic Shari'ah on the murder. Because it is an established practice in Libyan society, there is a necessity to assess it from the Islamic perspective and to ascertain whether it complies or contradicts the rules of the Shari'ah. The position of this research concerning this matter is guided by an important Islamic injunction: preventing mischief is better than bringing benefit. In addition to referring to Islamic literature, the researcher has utilized international humanitarian literature and treaties, Libyan law and relevant social studies. The research utilized the historical methodology to highlight the historical background for forced displacement. In addition, the researcher has used three interrelated approaches: the inductive, analytical and comparative in order to compare it with Islamic jurisprudence on this matter. The objective of this comparison is to see whether this custom is in agreement with recognized Islamic rules. The study also benefits from interviews people who had direct experience with conciliation sessions relating to the tradition of forced displacement. The most important lesson the study drawn for this study is the recognition of the rights of the murder victim's family as recognized under international humanitarian law. The study proposes an end to the forced displacement of the family of a convicted murderer in the absence of a clear Islamic and judicial ruling.